PENGARUH STRES KERJA DAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI DI SMP NEGERI 2 PAKIS KABUPATEN MALANG - EKO JUNI WAHYUDI; HASTIRIN WIDI ASTUTI (AKADEMIKA, 2023)
The purpose of this research aimed a) to find and analyze the effect of work stress and information technology on employee performance partially, b) to identify and analyze the effect of work stress and information technology on employee performance simultaneously, and c) to find out and analyze the dominant influence on employee performance. The population in this study was all employees of SMP Negeri 2 Pakis Kabupaten Malang, a total of 35 people. In this stud,y the researchers made the entire population (35 employees) as a sample which was 35 people. The data analysis method used in this research was multiple linear regression analysis. Research results showed; a) the variables of work stress and information technology had a partial effect on employee performance, b) variables of work stress and information technology simultaneously influenced employee performance, and c) information technology variable had the most dominant influences on the performance. Keywords: work stress, information technology, performance